Seismic reflection evidence for a Dangerous Grounds mini-plate in the South China Sea and implications for extrusion tectonics in SE Asia - Clift, Peter; Lee, Gwang H; Duc, Nguyen Anh; Barckhausen, Udo; Long, Hoang Van; Zhen, Sun (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1247 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.42